What members of the public think about taking part in medical research during an influenza pandemic: an international cross-sectional survey across eight OECD countries. (November 2018) - Gobat, Nina; Butler, Christopher C; Harris, Victoria; Gal, Micaela; Francis, Nicholas A; Mollison, Jill; Byrne, John-Paul; Watkins, Angela; Hood, Kerenza; Moore, Ronald; Sukumar, Prasanth; Webb, Steve A R; et al.
Abstract: Background: Patients and the public are primary beneficiaries and contributors to pandemic-relevant clinical research. We aimed to understand their views about participation in and enrolment to comparative effectiveness research in primary and critical care settings during an influenza pandemic. Methods: As part of the Platform for European Preparedness Against (Re-)emerging Epidemics (PREPARE), we conducted an international cross-sectional survey involving nationally representative samples of people in Belgium, Poland, Spain, Ireland, the UK, Canada, Australia, and New Zealand. Data were collected online using a scenario-based instrument during the 2017 regional influenza season. Scenarios involved research comparing routinely available treatments (low-risk research) and research to evaluate a new anti-viral treatment (higher risk). Descriptive and regression analyses were conducted. Findings: 6804 individuals responded to the survey, of whom 5572 (82%) supported pandemic-relevant research and 5089 (75%) thought that "special rules" should apply to make it happen. Between 62% (Belgium, 530 of 850) and 67% (Spain, 572 of 850) of respondents would participate in low-risk primary care research. 48% (New Zealand, 408 of 850) to 58% (Australia, 491 of 851) would participate in a higher-risk primary care scenario. Between 66% (Spain, 558 of 850) and 75% (Australia, 639 of 851) of respondents would participate in low-risk intensive care unit (ICU) research. 54% (Spain, 445 of 850) to 66% (Australia, 559 of 851) would take part in a higher-risk ICU scenario. Therapeutic misconception was predictive of willingness to participate in all research scenarios (primary care low risk odds ratio 8·56 [95% CI 6·61–11·07], p<0·0001; primary care higher risk 2·71 [2·11–3·48], p<0·0001; ICU low risk 4·41 [3·40–5·72], p<0·0001; ICU higher risk 1·52 [1·17–1·98], p=0·0016). Standard enrolment procedures were preferred by 3972 respondents (58%) for primary care but alternatives were acceptable to a substantial minority (2347, 34%). For the ICU scenario, 2623 (39%) preferred deferred consent and 2800 (41%) prospective third-party consent. 5256 respondents (77%) supported excess from samples collected during the pandemic being used for pandemic-relevant research during the pandemic and 4871 (72%) after. Greater pandemic knowledge, greater trust in a health professional, greater trust in government, and having had some ICU experience were factors predictive of willingness to participate in primary care and ICU scenarios, acceptability of alternative enrolment procedures, and willingness to donate excess from clinical samples for pandemic-relevant research. Interpretation: The public support pandemic-relevant clinical research. Public education, engagement, and policy initiatives to build research literacy are required to include a broader section of the population. Funding: European Commission's FP7 programme (grant agreement 602525) for PREPARE, St Vincents Anaesthetic Foundation, Cardiff University.